Python programming : an introduction to computer science - Zelle, John M. (Sherwood, Or. : Franklin, Beedle & Associates, 2010)
"Introduces computer programming using the Python programming language"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Python (Computer program language)